Effects of schema group therapy in older outpatients: a proof of concept study‡. (October 2014) - Videler, A. C.; Rossi, G.; Schoevaars, M.; van der Feltz-Cornelis, C. M.; van Alphen, S. P. J.
ABSTRACT Background: Short-term group schema cognitive behavior therapy (SCBT-g) showed improvements in overall symptomatology, early maladaptive schemas (EMS) and schema modes, both in adults and adolescents with personality disorder (PD) features and long-standing mood disorders. However, no research has yet been carried out on the effect in older adults. Therefore, in a proof of concept study, we explored the effect of SCBT-g in older outpatients with PD features and longstanding mood disorders. Method: Thirty-one older outpatients, aged 60–78 years with PD features and/or longstanding mood disorders were included in a proof of concept study with pre-mid-post design. Primary outcome was psychological distress (Brief Symptom Inventory) and intermediate outcomes were EMS (Young Schema Questionnaire) and schema modes (Schema Mode Inventory), assessed at baseline, mid-treatment and end-of-treatment. Paired samples t-tests were conducted, and Cohen's d effect sizes reported for pre mid- and post-treatment. As proof of concept analysis, hierarchical regression analyses with residual change scores were used to analyse whether early process changes in EMS (intermediate outcomes) predicted later outcome changes in symptoms. Results: SCBT-g led to significant improvement in all three measures of psychological symptoms, EMS and modes with medium effect sizes. Pre-treatment to mid-treatment changes in schema severity predicted symptom improvement from mid- to end-of-treatment. Conclusion: This proof of concept study shows that SCBT-g has potential to change EMS and to show significant effect at symptom level in older outpatients with PD features. A control condition in a randomized controlled trial is a necessary step for further research.